Investment-centric project management : advanced strategies for developing and executing successful capital projects - Keays, Steven, 1963- (J. Ross Publishing, 2017)
A comprehensive methodology and management system, this advanced reference offers project owners and developers alike a road map to predictable and repeatable project success, and a guarantee of future investment returns from their assets. -- Edited summary from book.
Keywords: Project management.; Project management -- Finance.; Investments.; Capital investments.; elektronické knihy; electronic books